2013
DOI: 10.1073/pnas.1220748110
|View full text |Cite
|
Sign up to set email alerts
|

BACE2 processes PMEL to form the melanosome amyloid matrix in pigment cells

Abstract: Amyloids are often associated with pathologic processes such as in Alzheimer's disease (AD), but can also underlie physiological processes such as pigmentation. Formation of pathological and functional amyloidogenic substrates can require precursor processing by proteases, as exemplified by the generation of Aβ peptide from amyloid precursor protein (APP) by beta-site APP cleaving enzyme (BACE)1 and γ-secretase. Proteolytic processing of the pigment cell-specific Melanocyte Protein (PMEL) is also required to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
166
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(184 citation statements)
references
References 42 publications
(67 reference statements)
12
166
1
Order By: Relevance
“…90 Other examples for functional amyloids in humans are amyloid fibers that serve as templates for the biosynthesis of melanin. [91][92][93] Furthermore, it has been shown that human serum albumin, lysozyme and other native proteins have a predisposition under certain situations to give way to amyloid fibril structures. 94,95 It is conceivable that the transition of a non-fibrillar protein to a self-aggregated amyloid fibrillar state does not necessarily only play a role in disease pathogenesis but also has a key function in signalling, communication and memorystorage.…”
Section: Amyloidogenesis: a Highly Organized Protein-peptide Aggregatmentioning
confidence: 99%
See 2 more Smart Citations
“…90 Other examples for functional amyloids in humans are amyloid fibers that serve as templates for the biosynthesis of melanin. [91][92][93] Furthermore, it has been shown that human serum albumin, lysozyme and other native proteins have a predisposition under certain situations to give way to amyloid fibril structures. 94,95 It is conceivable that the transition of a non-fibrillar protein to a self-aggregated amyloid fibrillar state does not necessarily only play a role in disease pathogenesis but also has a key function in signalling, communication and memorystorage.…”
Section: Amyloidogenesis: a Highly Organized Protein-peptide Aggregatmentioning
confidence: 99%
“…Briefly, the melanin precursor (MP) is activated by a tyrosinase (T) resulting in the activated melanin precursor (AMP), which interacts with the amyloidogenic sequence PmeI17 (PmeI) leading to mature melanin. [91][92][93] assembled to microtubes, has been explored for effectively deliver drugs. Using rhodamine as a model drug, it was shown that the FF microtubes released the drug in a steady-state profile, following first-order kinetics.…”
Section: Amyloid-based Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…1A). A subsequent proteolytic cleavage by BACE2 within endosomes (33) or by an ADAM (a disintegrin and a metalloproteinase) protease at the plasma membrane (34) cleaves M␤ into two fragments; the C-terminal fragment (CTF) contains the transmembrane domain and is eventually degraded in a ␥-secretase-dependent manner in lysosomes (35), whereas the other fragment (M␤Ј) is liberated from the membrane covalently bound to M␣ (33,36). No longer anchored to the membrane, most of the M␣ polymerizes into amyloid fibrils within endosomes (30,37) and concomitantly or subsequently undergoes additional proteolytic processing events to form smaller fragments; some of these fragments, called M␣Ј, are derived from the central RPT domain and are detected within preparations of the parallel arrays of functional amyloid fibrils characteristic of early stage melanosomes (27,29,38).…”
mentioning
confidence: 99%
“…No longer anchored to the membrane, most of the M␣ polymerizes into amyloid fibrils within endosomes (30,37) and concomitantly or subsequently undergoes additional proteolytic processing events to form smaller fragments; some of these fragments, called M␣Ј, are derived from the central RPT domain and are detected within preparations of the parallel arrays of functional amyloid fibrils characteristic of early stage melanosomes (27,29,38). Proprotein convertase and BACE2 cleavage are necessary for functional amyloid fibril formation, as interference with either of these two proteolytic processing events results in the formation of disordered PMEL aggregates instead of ordered fibrils (30,33). However, these cleavage events are not sufficient to induce fibril formation because a small fraction of cleaved PMEL is secreted from cells in culture (26,36,39) in a non-amyloid form.…”
mentioning
confidence: 99%